Experimental Investigation of Oxy-Hydrogen Injection in Natural Gas/Diesel Dual-Fuel Engine: Performance and Emission Analysis under Low Load Operation - Ariani, Betty; Felayati, Frengki Mohamad; Batutah, Mohammad Arif (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2024)
The pursuit of achieving zero carbon emissions by 2050 has led to the implementation of green technologies in the maritime industry. One crucial aspect is the adoption of alternative fuels, with a focus on non-fossil fuels to enhance energy efficiency and minimize emissions during ship operations. This study explores the innovative dual fuel diesel – Compressed Natural Gas (CNG) technology, which offers relatively low emissions with uncomplicated modifications to the diesel engine. CNG is injected into the intake manifold, addressing the need for cleaner fuel options. However, the evolution of this technology has encountered challenges such as methane slip resulting from incomplete combustion. This research proposes an intervention using hydrogen within the combustion chamber to improve combustion quality. Oxy-hydrogen gas (HHO), a carbon-free fuel derived from water through electrolysis, is considered as a potential solution. The utilization of HHO serves as a substitute for pure H2 due to its more feasible production and application, considering the global limitations in hydrogen storage and usage in transportation. The study aims to investigate the impact of HHO on the performance and emissions of dual fuel engines. Experimental tests are conducted under low loads to simulate critical operational points of the engine. Results indicate that the dual fuel system exhibits significant fuel savings, particularly with increasing injection duration. However, the need for additional oxygen to enhance combustion perfection must be balanced. HHO injection demonstrates the potential to improve engine performance, leveraging the oxygen content in HHO and the positive characteristics of hydrogen with its high Lower Heating Value (LHV). Furthermore, the research suggests that HHO injection can mitigate methane slip issues associated with dual fuel engine operations, offering a promising avenue for emission reduction